2011
DOI: 10.1016/j.neuroimage.2010.12.054
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical spatial patterns in Turner syndrome

Abstract: Turner syndrome (TS) is a highly prevalent genetic condition caused by partial or complete absence of one X-chromosome in a female and is associated with a lack of endogenous estrogen during development secondary to gonadal dysgenesis. Prominent cognitive weaknesses in executive and visuospatial function in the context of normal overall IQ also occur in affected individuals. Previous neuroimaging studies of TS point to a profile of neuroanatomical variation relative to age and sex matched controls. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
40
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 41 publications
11
40
0
5
Order By: Relevance
“…Overall, our results replicate most previous findings regarding structural abnormalities seen in adults and adolescent with TS, namely enlargement of the hippocampus and amygdala (Good et al, 2003; Kesler et al, 2004), reductions of GMV and WMV in the parieto-occipital and postcentral cortical regions (Brown et al, 2004; Cutter et al, 2006; Holzapfel et al, 2006; Marzelli et al, 2011), enlargement of the temporal gyri and insula (Kesler et al, 2003; Cutter et al, 2006; Marzelli et al, 2011), as well as increased cortical thickness in the temporal regions (Raznahan et al, 2010: Lepage et al, 2012). Our study also shows the existence of abnormal surface area in TS, as reduced surface area is observed in both TS groups in the postcentral, superior parietal, and entorhinal regions, coupled with an increase of surface area in the insular cortex visible in the X m group.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Overall, our results replicate most previous findings regarding structural abnormalities seen in adults and adolescent with TS, namely enlargement of the hippocampus and amygdala (Good et al, 2003; Kesler et al, 2004), reductions of GMV and WMV in the parieto-occipital and postcentral cortical regions (Brown et al, 2004; Cutter et al, 2006; Holzapfel et al, 2006; Marzelli et al, 2011), enlargement of the temporal gyri and insula (Kesler et al, 2003; Cutter et al, 2006; Marzelli et al, 2011), as well as increased cortical thickness in the temporal regions (Raznahan et al, 2010: Lepage et al, 2012). Our study also shows the existence of abnormal surface area in TS, as reduced surface area is observed in both TS groups in the postcentral, superior parietal, and entorhinal regions, coupled with an increase of surface area in the insular cortex visible in the X m group.…”
Section: Discussionsupporting
confidence: 90%
“…For structural data, whole brain characteristics including total cortical GMV, subcortical GMV, total WMV, total surface area, mean cortical thickness and cerebellar volume were investigated using ANCOVA with age and total brain volume as covariates. Total brain volume was defined as total gray and white matter tissue within the cerebrum in order to exclude the larger ventricles sometimes observed in the TS population (Marzelli et al, 2011). Results of the individual cortical regions pertaining to GMV, WMV, surface area and cortical thickness were investigated using ANCOVAs with group as a fixed factor, and age, total brain volume and FSIQ as covariates.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, a recent systematic review (Raznahan et al, 2010) and subsequent MRI studies in TS (Lepage et al, 2012; Marzelli et al, 2011) have identified replicated foci of anatomical difference between XO and XX humans, which we now show to be significantly altered in XO mice relative to their XX littermates, including the parietal cortex and striatum. Since these shared anatomical alterations in human and murine X-monosomy occur despite the lack of overt ovarian dysgenesis in murine X-monosomy, they potentially point towards a regionally-specific and evolutionarily preserved role for X chromosome genes on brain development.…”
Section: Discussionsupporting
confidence: 53%
“…We performed leave-one-out linear support vector machine (SVM) analyses (regularization parameter C=1) using in-house Matlab-based (Mathworks, Natick MA) tools which adopts LIBSVM (http://www.csie.ntu.edu.tw/~cjlin/libsvm/), and has been used successfully in several prior studies (Gothelf, et al, 2011; Hoeft, et al, 2008; Hoeft, McCandliss, et al, 2011; Hoeft, Walter, et al, 2011; Marzelli, Hoeft, Hong, & Reiss, 2011). First, we constructed a class vector constituting either ‘+1’s and ‘−1’s assigning each of the child from the three groups to either class label depending on the analysis.…”
Section: Methodsmentioning
confidence: 99%